Ground heat exchangers—A review of systems, models and applications - Florides, Georgios A.; Kalogirou, Soteris A. (My University, 2007)
The temperature at a certain depth in the ground remains nearly constant throughout the year and the ground capacitance is regarded as a passive means of heating and cooling of buildings. To exploit effectively the heat capacity of the ground, a heat-exchanger system has to be constructed. This is usually an array of buried pipes running along the length of a building, a nearby field or buried vertically into the ground. A circulating medium (water or air) is used in summer to extract heat from the hot environment of the building and dump it to the ground and vice versa in winter. A heat pump may also be coupled to the ground heat exchanger to increase its efficiency. In the literature, several calculation models are found for ground heat exchangers. The main input data are the geometrical characteristics of the system, the thermal characteristics of the ground, the thermal characteristics of the pipe and the undisturbed ground temperature during the operation of the system. During the first stages of the geothermal systems study, one-dimensional models were devised which were replaced by two-dimensional models during the 1990s and three-dimensional systems during recent years. The present models are further refined and can accommodate for any type of grid geometry that may give greater detail of the temperature variation around the pipes and in the ground. Monitoring systems have been set up to test various prototype constructions with satisfactory results.
Keywords: Ground heat exchangers; Ground temperature; Heat exchanger models; Ground source heat pump